Recognition of a status acquired abroad: Austria - Heindler , Florian; Melcher , Martina (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
CJEU and ECtHR case law generally oblige the EU Member States to recognise a status acquired abroad. This report shows in detail how Austrian law complies with this obligation and how ‘recognition’ is ensured in Austrian practice. Two general observations can be made: First, public policy considerations and the recognition of foreign administrative decisions and certificates (e.g. birth certificate) play an increasingly important role. Second, whereas much attention is paid to the result, namely the (non-)recognition of a status in Austria, methodologically sound arguments and justifications are missing in practice